'I do not know': an examination of reactions to virtual agents that fail to answer the user's questions - Söderlund, Magnus (The International review of retail, distribution and consumer research, 2024)
Virtual agents (VAs) used by retailers for online contacts with customers are becoming increasingly common. So far, however, many of them display relatively poor performance in conversations with users - and this is expected to continue for still some time. The present study examines one aspect of conversations between VAs and humans, namely what happens when a VA openly discloses its knowledge gaps versus when it makes attempt to conceal them in a setting in which it cannot answer user questions. A between-subjects experiment with a manipulated VA, and with perceived service quality as the main dependent variable, shows that a display of a high level of ability to answer user questions boosts perceived service quality. The study also offers explanations of this outcome in terms of mediating variables (perceived VA competence, openness to disclose own knowledge limits, usefulness, and learning-related benefits).